(3haGI SdjeGf GdaGQSis ((3eMeO s)
(3ChdgG (B:s
(3HGSfGO GdTjN CHh GdMSf GdgeOGfi Yf GdCUHZ Hf fHGJg bGd cfJ eY SdjeGf GdaGQSi QVi Gddg Yfg hcGf hGdjkG Ydi GdeOGFf ef bHd CejQ GdeDefjf bGd GdCUHZ aCJJg jhekG RGFQkG hbO eQV eQVg GdPi Jhai ajg s
(3BNQgG (B:s
(3hZPG fMf HGdchaI hGdefGOi jfGOi dUdGI GdeZQH hgPG eG GfJgi EdjfG ef MOjK haGI SdjeGf GdaGQSi hcdGeg ddejJ hcdGe GdejJ dg Ydi GdJeGe hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs